1988
DOI: 10.1149/1.2095349
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Cells with Modified MnO2 Cathodes

Abstract: The recent invention of rechargeable "modified" manganese oxide materials paves the way to the development of secondary batteries suitable for numerous applications. This includes alternatives to primary dry cells, and secondary lead/ acid and nickel-cadmium batteries. Present results describe the performance of cells in which the modified materials are coupled with zinc and iron. As opposed to iron which does not affect the longevity and capacity retention of the modified electrodes, zinc has a pejorative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 2 publications
0
49
1
Order By: Relevance
“…As the active material loading decreases, the internal resistance decreases and the capacity utilization and working voltage increase. Wroblowa et al [8,26] who reported a cycling of 1.9 electrons at 10% active material loading. Hence this could be accounted for the observed higher discharge capacity.…”
Section: Resultsmentioning
confidence: 99%
“…As the active material loading decreases, the internal resistance decreases and the capacity utilization and working voltage increase. Wroblowa et al [8,26] who reported a cycling of 1.9 electrons at 10% active material loading. Hence this could be accounted for the observed higher discharge capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The mentioned processes in alkaline cells are based on several electrochemical reactions of Mn oxides, particularly on electrochemical redox cycling of Mn IV /Mn III /Mn II , and possibly on chemical reactions of the reduced Mn species with oxygen [27][28][29][30][31][32]. Figure 10 depicts the typical cyclic voltammograms of MnO 2 //C alkaline cells using undoped-and doped-MnO 2 cathode materials.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…The electrochemical discharge of electrodeposited manganese dioxide (EMD) can be represented as follows [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]:…”
Section: Introductionmentioning
confidence: 99%
“…We thus expect that MnO 2 would satisfy the requirements for the positive electrode of the FCB system as it can be charged by oxygen gas and by the supply of electric power. Many papers have reported rechargeable manganese dioxide electrodes in aqueous solutions by restricting the depth of discharge [25,26,42], by adding metals [26][27][28][29][30][31][32][33][34][35]42] and by oxygenregeneration of the discharged manganese dioxide electrodes (MnOOH) [40][41][42][43]. However, few studies exist describing the gaseous charging of discharged manganese dioxide (MnOOH) by oxygen.…”
Section: Introductionmentioning
confidence: 99%